Non-targeted Metabolomics Profiling of Plasma Samples From Patients With Major Depressive Disorder - Wu, Zhonghao; Yu, Heming; Tian, Yu; Wang, Yue; He, Yong; Lan, Tianlan; Li, Yan; Bai, Mengge; Chen, Xiangyu; Chen, Zhi; Ji, Ping; Zhang, Hongmei; et al. (Frontiers in Psychiatry, 2022)
Background: Major depressive disorder (MDD) is a neuropsychiatric disorder caused by multiple factors. Although there are clear guidelines for the diagnosis of MDD, the direct and objective diagnostic methods remain inadequate thus far. Methods: This study aims to discover peripheral biomarkers in MDD patients and promote the diagnosis of MDD. Plasma samples of healthy controls (HCs, n=52) and MDD patients (n=38) were collected, and then metabolism analysis was performed using ultrahigh-performance liquid chromatography tandem mass spectrometry (LC–MS/MS). Heatmap analysis was performed to identify the different metabolites. Meanwhile, receiver operating characteristic (ROC) curves of these differential metabolites were generated. Results: Six differential metabolites were found by LC–MS/MS analysis. Three of these were increased, including L-aspartic acid (Asp), diethanolamine and alanine. Three were decreased, including O-acetyl-L-carnitine (LAC), cystine, and fumarate. Additionally, LAC, Asp, fumarate and alanine showed large areas under the curve (AUCs) by ROC analysis. Conclusions: The study explored differences in peripheral blood between depressed patients and healthy controls. These results indicated that differential metabolites with large AUCs may have the potential to be promising biomarkers for the diagnosis of MDD.